Clinical characteristics and treatment outcomes of cervical high-grade squamous intraepithelial lesions in women under 25 years: a retrospective cohort study - Liu, Yanmei; Peng, Ke; Gao, Shujun (Frontiers in Oncology, 2025)
ObjectivesLimited data are available regarding the clinical characteristics and treatment outcomes of cervical HSIL in women under 25, particularly in Asian populations. This study aimed to investigate the clinical features of cervical HSIL in women under 25 and to compare the efficacy of various treatment modalities, with the goal of informing early detection and optimal management strategies.MethodsA retrospective cohort study was conducted involving 210 patients under 25 who were diagnosed with cervical HSIL at Obstetrics and Gynecology Hospital of Fudan University between January 2019 and December 2021. Data on clinical features, cytology, HPV status, colposcopy findings, and treatment approaches were collected and analyzed. Treatment outcomes were assessed by comparing postoperative cytology, HPV clearance, and pathological results at 6 and 12 months among patients managed with observation, CO2 laser therapy, or LEEP.ResultsMost patients (89.0%) were diagnosed via routine screening and 86.7% were asymptomatic. Among symptomatic cases, postcoital bleeding (10.0%) and abnormal vaginal discharge (3.3%) were reported. Cytology showed NILM in 38.1%, ASCUS 30.5%, LSIL 21.0%, HSIL 7.1%, and ASC-H 3.3%. HPV was detected in 98.1% of patients, predominantly HPV16 (65.2%). Cytology alone showed low sensitivity for detecting cervical HSIL (7.1%) compared with HPV testing (98.1%) or co-testing (98.6%, χ²=534.468, P<0.001). At 12-month follow-up, the LEEP group exhibited the highest rates of normal cytology (90.5%), HPV clearance (87.5%), and histologic cure (95.2%), outperforming both the laser and observation groups. Multivariate logistic regression analyses identified reproductive tract inflammation as an independent risk factor for persistent high-risk HPV infection among patients undergoing observation.ConclusionsMost cervical HSIL under 25 are asymptomatic. Cytology alone is insufficient for reliable detection, HPV based screening significantly improves sensitivity. Among treatment strategies, LEEP offers the most effective histological cure rate, although potential reproductive risks warrant careful consideration in nulliparous women.